Awareness on periodontal aesthetic procedures among dental students in a private dental college in Chennai- A questionnaire based survey (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Periodontics is that speciality of dentistry which deals with the soft and hard tissues supporting the tooth structure and is one of the fastest growing dental specialties. Less attention has been given to soft tissue esthetics, the shape of the face and position of the lips, and the contours, color, and overall appearance of the gingiva and associated soft tissues.Aim: The aim of this questionnaire based survey was to assess the degree of awareness on periodontal aesthetic procedures among dental students in a private dental college in Chennai.Materials and Methods: This was a cross-sectional descriptive survey which was conducted from october 2020 to march 2021. Questionnaires consisting of 13 questions related to different periodontal aesthetic procedures along with demographic details were used , the responses were then tabulated followed by statistical analysis was done using SPSS software. Descriptive statistics in the form of percentages and ratios were performed for all the questions and the chi-square test was used to detect significant associations among undergraduates and postgraduates.Results: There were no statistical significant differences between the awareness on periodontal aesthetic procedures between the undergraduates and postgraduate students,( Chi square analysis ; p value >0.05)in all the questions between undergraduate and postgraduate students.Conclusion: Within the limitations of the study it can be concluded that there was no significant difference in awareness between undergraduates and postgraduates implying both undergraduate and postgraduate dental students were mostly aware of the periodontal aesthetic procedures.